Regulation of Inflammatory Responses to Bordetella Pertussis by NG-Monomethyl-L-Arginine in Mice Intranasally Infected - D. Torre; F. Speranza; A. Pugliese; G. Fassina; A. Osculati; L. Perversi; M. G. Banfi; M. Airoldi (Mediators of Inflammation)
To investigate effect of MMLA, an inhibitor of nitric oxide (NO) production, on regulation of inflammatory responses to Bordetella pertussis infection, mice were infected intranasally, and treated with various concentrations of MMLA. Ten days after infection, mice treated with MMLA at dosage of 100 mg/kg, given intraperitoneally in a single dose or for 5 consecutive days, showed at histopathologic examination, a significant decrease of intensity of inflammation (scores, 0.6±0.2 and 0.9±0.5 respectively). A decrease of cellular accumulation of neutrophils and lymphocytes in the bronchoalveolar lavage (BAL) fluid was observed in infected mice treated with MMLA, especially at dosage of 10 mg/kg, given in a single dose intraperitoneally. In addition, BP-infected mice treated with MMLA (100 mg/kg, intraperitoneally) for 5 consecutive days showed higher mortality rate than untreated mice infected with B. pertussis, and the number of B. pertussis in lungs of mice treated with MMLA was significantly increased. However, MMLA treatment of infected mice had some effect on levels of IFN-γ and nitrite/nitrate (end-stable products of NO) in the BAL fluid. This study indicates that NO may play a role either as microbiocidal agent or as a modulator of immune regulation, inasmuch as it may upregulate tissue inflammatory response to B.pertussis.